Remote sensing in resource geography - Saini, R. R.; Kalwar, S. C. (Jaipur, India : Pointer Publishers, Distributed by Aavishkar Publishers' Distributors, 1991)
Study based on Jaipur District, Rajasthan.
Includes bibliographical references
Keywords: Remote sensing -- India | -- Jaipur (District)